Entropy Solutions for Nonlinear Elliptic Anisotropic Homogeneous Neumann Problem - B. K. Bonzi; S. Ouaro; F. D. Y. Zongo (International Journal of Differential Equations)
We prove the existence and uniqueness of entropy solution for nonlinear anisotropic elliptic equations with Neumann homogeneous boundary value condition for -data. We prove first, by using minimization techniques, the existence and uniqueness of weak solution when the data is bounded, and by approximation methods, we prove a result of existence and uniqueness of entropy solution.